2007
DOI: 10.1002/anie.200701650
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic Substitution at Phosphorus for the Synthesis of Alkyl and Aryl Phosphanes

Abstract: A transition‐metal‐free radical phosphonation using Me3SnPPh2 and the less toxic Me3SiPPh2 is reported. These readily available reagents react highly efficiently with primary and secondary alkyl radicals. Moreover, aryl radicals and tertiary alkyl radicals are phosphonated with Me3SnPPh2 (see scheme; R=aryl, alkyl, vinyl; X=I, Br, OC(S)imidazolyl). DFT calculations provide insights into the mechanism of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Radical alkylphosphanylation of olefins has recently been described using stannylated and silylated phosphanes. Homolytic substitution at phosphorus with alkyl and aryl radicals is a relatively fast process [33], allowing the addition of an alkyl group and a phosphorus derivative across the π-system of an activated olefin. This is illustrated below with the three-component reaction involving t-butyl iodide, acrylonitrile, and Me 3 SnPPh 2 (Scheme 14.11) [34].…”
Section: Carbohydroxylation Sulfenylation and Phosphorylation Of Olmentioning
confidence: 99%
“…Radical alkylphosphanylation of olefins has recently been described using stannylated and silylated phosphanes. Homolytic substitution at phosphorus with alkyl and aryl radicals is a relatively fast process [33], allowing the addition of an alkyl group and a phosphorus derivative across the π-system of an activated olefin. This is illustrated below with the three-component reaction involving t-butyl iodide, acrylonitrile, and Me 3 SnPPh 2 (Scheme 14.11) [34].…”
Section: Carbohydroxylation Sulfenylation and Phosphorylation Of Olmentioning
confidence: 99%
“…4 For our part, we have previously shown that the three-coordinate titanium(III) complex Ti(N[ t Bu]Ar) 3 (Ar = 3,5-C 6 H 3 Me 2 ), 1, is a potent halogen-atom abstractor, capable of abstracting X· (X = Cl, Br, or I) from various donor molecules at room temperature or below, in aprotic organic media (Figure 1). With the present work, we sought to develop a high-yield synthesis of phosphines PR 3 from 3 RX and 0.25 P 4 , using Ti(N[ t Bu]Ar) 3 as a halogen atom sink (see idealized Equation 1).…”
mentioning
confidence: 95%
“…[24] Considering the importance of ortho-substituted arylphosphanes,l ithiation and subsequent trapping of the intermediate Li species with electrophiles was studied (Scheme 4). Sn-Li exchange of 3a with MeLi in THF and treatment with chlorodiarylphosphanes afforded the bisphosphanes 6 and 7 in good yields.T rapping with panisaldehyde (8), borylation (9), acylation( 10), formylation (11), and aminomethylation (12)worked equally well. Moreover, the Pa tom in 3a was readily protected upon oxidation with H 2 O 2 to give phosphane oxide 13.…”
mentioning
confidence: 88%